2015
DOI: 10.1074/jbc.m115.662940
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor PAX6 (Paired Box 6) Controls Limbal Stem Cell Lineage in Development and Disease

Abstract: Background: PAX6 is a master regulatory gene involved in eye development. Results: PAX6 is expressed in the primitive eye cup and later in corneal tissue progenitors in early embryonic development. Conclusion: PAX6 plays a critical role in limbal stem cell and corneal epithelial fate determination. Significance: These findings provide important insight into corneal homeostasis and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…PAX6, a protein initially found to regulate neural stem cell self-renewal and differentiation, marks progenitor cells in the developing lens, cornea and lacrimal glands (Li et al , 2015; Lin et al , 2016). PAX6 is essential for ocular organ formation as shown by the absence of eyes and lacrimal gland in Pax6−/− embryos (Hill et al , 1991) and impaired eye and lacrimal gland morphogenesis in embryos heterozygous for Pax6 (Makarenkova et al , 2000; Remez et al , 2017).…”
Section: Salivary Gland Developmentmentioning
confidence: 99%
“…PAX6, a protein initially found to regulate neural stem cell self-renewal and differentiation, marks progenitor cells in the developing lens, cornea and lacrimal glands (Li et al , 2015; Lin et al , 2016). PAX6 is essential for ocular organ formation as shown by the absence of eyes and lacrimal gland in Pax6−/− embryos (Hill et al , 1991) and impaired eye and lacrimal gland morphogenesis in embryos heterozygous for Pax6 (Makarenkova et al , 2000; Remez et al , 2017).…”
Section: Salivary Gland Developmentmentioning
confidence: 99%
“…An early eye field transcription factor, PAX6, can be first detected in the surface ectoderm of the developing mouse at embryonic (E) eight stage, and is subsequently expressed in the developing corneal epithelium at E12.5 . Recent genetic lineage tracing studies in Pax6/Cre (P0–3.9‐GFPCre) mice crossed to ROSA mT/mG reporter mice showed greed fluorescent protein (GFP) expression in the entire corneal epithelium suggesting that Pax6‐expressing progenitors contribute to corneal epithelial generation and regeneration during development and adulthood, which raised the possibility that Pax6+ cells within the surface ectoderm represent the cells of origin of LSC. This possibility is also supported by findings in Pax6+/− mice that revealed that Pax6 haploinsufficiency results in reduced expression of the corneal epithelial differentiation marker Krt12 and increased corneal vascularization consistent with a LSCD phenotype …”
Section: Developmental Origin Of Lsc and Their Nichementioning
confidence: 99%
“…[36][37][38] These factors might potentially affect the differentiation of surface ectoderm and mesoderm during embryonic eye development. Moreover, a recent study found that nicotine could induce CpG methylation of a PAX6-binding motif, and thus inhibit downstream steroid hormone production essential to antiinflammatory effect and fetal development; 10 this might potentially correlate to the PAX6 loss identified by Li et al 39 However, the exact mechanisms still remain unknown and need to be further investigated. Paternal smoking might also genetically affect sperm; 29 although little evidence is provided for this possible mechanism, it may offer a pathway to further investigate the genetic factors for ED in the future.…”
Section: Discussionmentioning
confidence: 98%
“…Paired Box 6 (PAX6) is a transcription factor that plays a key role in limbal stem cells and corneal epithelial fate determination and maintenance. 7,8 A recent study showed that PAX6 was completely absent from corneal dermoid tissue, suggesting its association with the pathogenesis of corneal dermoids, a subtype of ED; 9 nicotine is a potential environmental factor associated with this PAX6 absence. 10 Concerning genetic factors, most ED cases are considered sporadic.…”
Section: Introductionmentioning
confidence: 99%